2008
DOI: 10.1007/s00384-008-0478-0
|View full text |Cite
|
Sign up to set email alerts
|

Detailed evaluation of functional recovery following laparoscopic or open surgery for colorectal cancer within an enhanced recovery programme

Abstract: Within an enhanced recovery programme, patients undergoing laparoscopic surgery recovered more quickly than after open resection. Both approaches however, were associated with slow recovery despite a relatively short hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 13 publications
5
84
0
Order By: Relevance
“…Our mortality rate, anastomotic leaks and overall mortality are similar to the ones stated in other literature series [15][16][17][22][23][24][25] and the current use of fast-track protocols is more than justified, taking into account the clinical advantages offered and, as evidenced by our series, the overall stay of patients, with a median of six days, which is practically half of that shown in a recent study conducted by the Asociació n Españ ola de Cirujanos 26 [Spanish Association of Surgeons].…”
Section: Discussionsupporting
confidence: 92%
“…Our mortality rate, anastomotic leaks and overall mortality are similar to the ones stated in other literature series [15][16][17][22][23][24][25] and the current use of fast-track protocols is more than justified, taking into account the clinical advantages offered and, as evidenced by our series, the overall stay of patients, with a median of six days, which is practically half of that shown in a recent study conducted by the Asociació n Españ ola de Cirujanos 26 [Spanish Association of Surgeons].…”
Section: Discussionsupporting
confidence: 92%
“…Polle et al [12], King et al [9], Eshuis et al [11] and Maartense et al [10] reported a similar HRQOL within the first 3 months after surgery. There was no difference in long-term HRQOL outcomes (≥1 year) in the studies of Guillou et al [1], Eshuis et al [11] and Maartense et al [10].…”
Section: Discussionmentioning
confidence: 78%
“…Some authors reported no substantial differences in postoperative HRQOL [1,9,10,11,12], whereas other authors demonstrated significantly improved HRQOL outcomes after laparoscopic colorectal resection [4,13,14,15,16]. One of the last systematic reviews on the topic also discussed reasons for insufficient data and heterogeneity of the studies [6].…”
Section: Introductionmentioning
confidence: 99%
“…1), including 19 case-series studies and 7 nonrandomized controlled trials, leaving 4 randomized controlled trials. [17][18][19]26 One randomized controlled trial was excluded because no data were available for extraction to be used in the meta-analysis. 26 Finally, 3 randomized controlled trials were included for meta-analysis.…”
Section: Article Searchmentioning
confidence: 99%
“…[17][18][19]26 One randomized controlled trial was excluded because no data were available for extraction to be used in the meta-analysis. 26 Finally, 3 randomized controlled trials were included for meta-analysis. [17][18][19] Characteristics of each trial are given in Table 1.…”
Section: Article Searchmentioning
confidence: 99%